PERANAN GURU AGAMA HINDU DALAM PENGUATAN NILAI-NILAI TAT TVAM ASI BAGI SISWA HINDU DI SDN DWIPASARI KABUPATEN BARITO KUALA - Ida Ayu Sri Eka Gayatri; I Gede Dharman Gunawan; Luh Putu Muliani Handayani (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
Hindu students in the school environment still practice bad ethics such as behaving impolitely and politely, speaking that is not good to hear, students fighting, bullying each other, and being ignorant with their friends at school. Therefore, the role of Hindu religious teachers is important in strengthening Tat Tvam Asi values ​​for Hindu students at SDN Dwipasari, Wanaraya District, Barito Kuala Regency. With Hindu religious teachers providing reinforcement to students regarding the teachings of Tat Tvam Asi values, Hindu students will always have an ethical and polite behavior, have a mutual love for teachers and friends, and protect the natural environment around the school. This study aims to determine, analyze, and describe the role of Hindu religious teachers in strengthening Tat Tvam Asi values ​​for Hindu students. This study uses a qualitative method using purposive techniques in determining the informants who will be used as instruments. In data collection techniques, researchers used several methods, namely observation, interviews, and documentation. While the data analysis technique used includes three steps, namely data reduction, data presentation, and drawing conclusions. The results of the research are the role of Hindu religious teachers in strengthening Tat Tvam Asi values ​​for Hindu students, namely: roles as educators, teachers, mentors, role models, and motivators.